2018
DOI: 10.17977/um001v3i22018p059
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Website Cybercounseling Realita untuk Meningkatkan Keterbukaan Diri Siswa Sekolah Menengah Kejuruan

Abstract: This research and development aims to produce a cybercounseling reality website and a reality cybercounseling guidebook to improve self-disclosure for Vocational High School students which are grateful theoretically and practically. The research and development study steps are: preliminary study, product development, and product test. Product's guidelines are tested using one group pretest-posttest design. Product test results show that cybercounseling reality website is gratefully theoretically and practicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
3
0
7
Order By: Relevance
“…Asynchronous online therapy has been frequently implemented (Chester & Glass, 2006), along with synchronous online counseling carried out through chat and video conference (Bambling, King, Reid, & Wegner, 2008). In Indonesia, online counseling has been massively discussed (Ifdil & Ardi, 2013;Kirana, 2019;Prabawa, Ramli, & Fauzan, 2018;Prasetya, 2017) and many research on this topic has been reported (Bangun & Saragih, 2015;Mansyur, Badrujaman, Imawati, & Fadhillah, 2020;Prabawa et al, 2018;Prahesti & Wiyono, 2017;Setyawan, 2019;Sukoco KW & Budiman S, 2019;Sutijono & Farid, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Asynchronous online therapy has been frequently implemented (Chester & Glass, 2006), along with synchronous online counseling carried out through chat and video conference (Bambling, King, Reid, & Wegner, 2008). In Indonesia, online counseling has been massively discussed (Ifdil & Ardi, 2013;Kirana, 2019;Prabawa, Ramli, & Fauzan, 2018;Prasetya, 2017) and many research on this topic has been reported (Bangun & Saragih, 2015;Mansyur, Badrujaman, Imawati, & Fadhillah, 2020;Prabawa et al, 2018;Prahesti & Wiyono, 2017;Setyawan, 2019;Sukoco KW & Budiman S, 2019;Sutijono & Farid, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The first is a study on cyber counseling with the help of Facebook [18]. The second concerns the use of internet sites for cyber counseling with a Reality approach [19]. According to the study, the cyber counseling that they do can increase self-disclosure in vocational students.…”
Section: Resultsmentioning
confidence: 99%
“…Terdapat beberapa jenis layanan konseling online yang dapat ditemukan secara mudah oleh individu seperti website (Prahesti & Wiyono, 2017), pesan teks cepat (Duniawati, Muksin, & Lukman, 2020), telepon (Masi & Freedman, 2001), konferensi video (Prabawa, 2015), Instagram (Noviyanti, 2020), atau website yang dikembangkan sendiri (Prabawa, Ramli, & Fauza, 2018). Beberapa platform ini sudah dibuktikan efektif walau terdapat kekurangan dalam pelaksanaannya.…”
Section: Hasil Penelitian Dan Pembahasan Konseling Kelompok Onlineunclassified